Thermochemistry of double magnesium tellurite - Dyusekeeva, A.T.; Bekturganova, A.Zh.; Rustembekov, K.T.; Kasenov, B.K.; Makhatova, N.A.; Stoev, M. (KSU Publ., 2015)
The isobaric heat capacity of double magnesium tellurite is studied in the range of 298.15–673 K and used as a basis for deriving dependences Cºp~f (T) and determining their thermodynamic functions. Dependences Cºp~f (T) are found to have abnormally sharp λ-like peaks, due probably to second-order phase transitions.
Магний қос теллуритінің термохимиясы
Термохимия двойного теллурита магния
Keywords: calorimetry; heat capacity; magnesium tellurite; second-order phase transitions; thermodynamic functions